Genetic Taster Status as a Mediator of Neural Activity and Swallowing Mechanics in Healthy Adults - Dietsch, Angela M.; Westemeyer, Ross M.; Pearson, William G.; Schultz, Douglas H. (Frontiers in Neuroscience, 2019)
As part of a larger study examining relationships between taste properties and swallowing, we assessed the influence of genetic taster status on measures of brain activity and swallowing physiology during taste stimulation in healthy men and women. Twenty-one participants underwent videofluoroscopic swallowing studies (VFSS) and functional magnetic resonance imaging (fMRI) during trials of high-intensity taste stimuli. The precisely formulated mixtures included sour, sweet-sour, lemon, and orange taste profiles and unflavored controls. Swallowing physiology was characterized via computational analysis of swallowing mechanics plus other kinematic and temporal measures, all extracted from VFSS recordings. Whole-brain analysis of fMRI data assessed blood oxygen responses to neural activity associated with taste stimulation. Swallowing morphometry, kinematics, temporal measures, and neuroimaging analysis revealed differential responses by genetic taster status. Supertasters exhibited increased amplitude of most pharyngeal movements, and decreased activity in the primary somatosensory cortex compared to nontasters and midtasters. These preliminary findings suggest baseline differences in swallowing physiology and the associated neural underpinnings associated with genetic taster status. Given the potential implications for dysphagia risk and recovery patterns, genetic taster status should be included as a relevant variable in future research regarding swallowing function and dysfunction.